Investigation of Double-Layer Corrugated Steel Plate Shear Walls in Multi-Story Frames - Mahdi Kiani; Ali Mohammad Rousta; Hamed Enatyati (Journal of Rehabilitation in Civil Engineering)
Flat steel plate shear walls (FPSWs) are widely used in steel structures, but they are prone to buckling under lateral loads. As an alternative, corrugated steel plate shear walls (CPSWs) have been introduced, in which the infill flat steel plate is replaced with a corrugated steel plate. CPSWs have some advantages over FPSWs, such as improved in-plane and out-of-plane stiffness, buckling strength, and ductility. Nevertheless, their applicable thickness is limited due to manufacturing capabilities. In the last few years, to overcome this drawback, double-layer corrugated steel plate shear walls (DCPSWs) composed of two similar corrugated steel plates have been developed. As there are few studies on DCPSWs, mainly focused on single-story frames, this paper considers 48 two-dimensional multi-story frames with DCPSWs using the pushover method. According to the results, corrugated shear walls have less lateral strength compared to FPSWs. However, the difference decreases with increasing the number of stories. The corrugated shear walls have higher ductility, especially for low-rise frames. Furthermore, the frames with DCPSWs experienced the highest inelastic deformations, which can be considered an advantage over CPSWs.